A Scorecard for Assessing Functionality of Community Health Unit in Kenya - Ager, Duncan; Oele, George; Muhula, Samuel; Achieng, Susan; Emalu, Moses; Nanjala, Mildred; Kosgei, Sarah; Wanjiru, Susan; Ofware, Peter; Ojakaa, David; Ndirangu, Meshack; Kyomuhangi, Lennie (Pan African Medical Journal)
The Pan African Medical Journal. 2016;25 (Supp 2):10
© Duncan Ager et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited
Keywords: Scorecard, community health strategy, community health unit, functionality